Metabolite differences and molecular mechanism between dehiscent and indehiscent capsule of mature sesame - Yinping Zhang; Ruirui Chen; Yujun Liu; Shuwen Xu; Shuguang Gao; Haiyang Zhang; Hongmei Miao; Lingling Qin; Xiangyu Zhou; Kiran Thakur; Cheng Li; Juan Li; et al. (Food Chemistry: Molecular Sciences)
The loss of sesame capsule seed prior to harvest poses a significant economical challenge in mechanized production. The metabolites involved in capsule closure are still unclear. Using comparative metabolome and transcriptome analysis, this work investigated the molecular regulation and enrichment pathways in two sesame types of indehiscent capsule WanZhi28 (ND) and dehiscent capsule WanZhi2 (WZ2). The findings demonstrated that genes and metabolites were significantly enriched in lignin synthesis-related pathways. Furthermore, data suggests that lipid and sugar metabolism may have an impact on capsule closure. Apart from its function in cell signaling, the latter may contribute to the glycosylation of lignin monomers, while the former may provide ATP for cellular microtubule movement. This work concurrently focused on a large number of differentially expressed transcription factors linked to the sesame capsule's anti-cleft mechanism, providing new evidence for the discovery and use of functional markers and genes for capsule dehiscence. The identification of key pathways and regulatory mechanisms offers valuable information for developing strategies to mitigate seed loss during harvest, ultimately contributing to more efficient and profitable sesame production.